Competition for Jurisdiction Over Food Industry in South Korea - Sungeun Park (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2011)
In spite of the government’s multilateral effort to control food safety, there have been constantly many shock events threatening citizens’ health. This paper points out the matter of food safety management system with a view of competition for jurisdiction over food industry among the Ministry of Health and Welfare and the Ministry for Food, Agriculture, Forestry and Fisheries and affiliated organizations. Use description qualitative method in research. Each ministry has separate basic positions and approaches to food industry policy: regulation and promotion. The policy image has been changed into “regulation” as public anxiety and concern for hazardous foods has grown since the end of 1990. They competeto take charge of promoting or regulating the food industry by establishing or amending laws, expanding organizations and mobilizing a coalition. Coordination by policy committee, cooperation between agencies, and integration of agencies were introduced as measures to eliminate unnecessary competition for jurisdiction.